2020
DOI: 10.1002/ijc.33407
|View full text |Cite|
|
Sign up to set email alerts
|

Progress, challenges and ways forward supporting cancer surveillance in Latin America

Abstract: Population‐based cancer registries (PBCRs) are the only means to provide reliable incidence and survival data as a basis for policy‐making and resource allocations within cancer care. Yet, less than 3% and 10% of the respective populations of Central America and South America are covered by high‐quality cancer registries. The Global Initiative for Cancer Registry Development provides support to improve this situation via the International Agency for Research on Cancer Regional Hub for Latin America. In this pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 32 publications
0
19
0
3
Order By: Relevance
“…For instance, cancer registries cover only small proportions of the population (less than 10%) in Latin America and Asia, whereas the corresponding figure is 98% in the USA. [ 27 , 28 ] China's national cancer registry has made remarkable improvements in data representativeness and quality since its establishment in 2002. [ 29 ] The total number of local population-based cancer registries has increased significantly from 501 in 2015 to 1152 in 2020, presently covering up to 598 million people in China.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, cancer registries cover only small proportions of the population (less than 10%) in Latin America and Asia, whereas the corresponding figure is 98% in the USA. [ 27 , 28 ] China's national cancer registry has made remarkable improvements in data representativeness and quality since its establishment in 2002. [ 29 ] The total number of local population-based cancer registries has increased significantly from 501 in 2015 to 1152 in 2020, presently covering up to 598 million people in China.…”
Section: Discussionmentioning
confidence: 99%
“…Colombia, like most LMIC, does not have national PBCR, the regional PBCR cover together less than 15% of the population [ 16 ], and their source populations are relatively small. Strict personal data protection policies pose difficulties in linking vital statistics data with those from the PBCR [ 4 ], a situation shared with many LMIC.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported the impact of incomplete registration and inclusion of death-certificated-only (DCO), death-certificate-notified (DCN), and death certificate-initiated (DCI) cases [ 6 , 9 11 ] and others on the impact of completeness of follow-up over cancer survival [ 7 , 8 , 12 15 ] employing real data from PBCR and hospital populations or simulations. However, the studies that evaluated impact of LFU on survival considered sample sizes over ≥1,000 cases, whereas PBCR in LMIC are usually regional with relatively small sizes (populations of around 300,000 to 1.5 million inhabitants, implying less than 500 cancer cases for individual cancer during a 5-year period) [ 16 ], and there is no information regarding the impact in such situations with few cases. Studies with simulated data artificially create a “perfect registry” where the artificial truth is known; however, these do not necessarily mimic demographic patterns, and their relations with prognoses that are similar to “real-life” situations and LFU patterns could be hard, and conclusions could be nonspecific.…”
Section: Introductionmentioning
confidence: 99%
“…Fourth, it is possible to actively identify cases with lung cancer over the entire of population of patients attending to different providers. Finally, it is paramount to point out that these methods for identifying and estimating prevalence rates could help other LMICs to optimize their epidemiological surveillance system and to understand its impact in a context with different characteristics, compared to the developed world [27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%